THE ROLE OF INNOVATIVE TECHNOLOGIES IN THE SCIENCE LESSON IN THE DEVELOPMENT OF THE NEW WORLD - Orazaliyeva Gulvira Sapakovna; Sadvakasova Gulnur Turarbekovna (Scientific Research and Experimental Development, 2024)
The article discusses the role of innovative technologies in science lessons in the development of a new world. Innovative technologies are discussed, which include a fairly wide group of methods and techniques for organizing the pedagogical process